2016
DOI: 10.1371/journal.pone.0153167
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Ferritin Levels and Dyslipidemia in Korean Adolescents

Abstract: BackgroundFerritin is associated with various cardiometabolic risk factors such as dyslipidemia, hypertension, obesity, and insulin resistance in adults. We aimed to study the association between serum ferritin levels and dyslipidemia in adolescents, because dyslipidemia is considered an important modifiable cardiovascular risk factor in the young.MethodsWe analyzed 1,879 subjects (1,026 boys and 853 girls) from the 2009–2010 Korean National Health and Nutrition Examination Survey IV. Subjects were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
8
33
0
Order By: Relevance
“…Previous studies debated on the associations between high SF and dyslipidemic parameters among participants of different ages, sexes, body sizes and ethnic distributions. Kim et al found that in Korean adolescents, SF was positively correlated with TC, TG, and LDL-C levels only in boys, but negatively correlated with HDL-C in both boys and girls [44]. In a Finnish study of adults, SF was shown to be correlated with markers of cardiometabolic risk (elevated TG, apoB, and reduced HDL-C) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies debated on the associations between high SF and dyslipidemic parameters among participants of different ages, sexes, body sizes and ethnic distributions. Kim et al found that in Korean adolescents, SF was positively correlated with TC, TG, and LDL-C levels only in boys, but negatively correlated with HDL-C in both boys and girls [44]. In a Finnish study of adults, SF was shown to be correlated with markers of cardiometabolic risk (elevated TG, apoB, and reduced HDL-C) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that ferritin levels are associated with metabolic syndrome in children and adolescents [ 4 ]. In adults, ferritin levels are independently associated with a high prevalence of dyslipidemia [ 5 ], non-alcoholic fatty liver disease [ 6 ], insulin resistance [ 7 ], and stroke [ 8 ]. In addition, some studies have suggested that SF also has a role in the development of central obesity [ 9 ], hypertension [ 10 ], type 2 diabetes mellitus [ 11 ], and coronary artery disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Apart from these effects, the recent research suggests that raised ferritin levels in the body is also associated with metabolic derangements in the body. 9 Lipids are regarded as an important source of energy in the body. 10 They have a necessary role in signaling metabolites in body.…”
Section: Introductionmentioning
confidence: 99%
“…6 Sometimes, in certain hereditary conditions, the lipid profile may be deranged since childhood. 9 Unluckily, in such cases, it causes premature cardiovascular diseases in young age and is associated with poor prognosis. 9 The recent research and clinical data proposes that there is a link between regulatory processes of ferritin and lipids in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation